Old city hall eaudiobook Detective ari greene series, book 1. - Rotenberg, Robert (Detective Greene, 2009)
A noted criminal defense attorney, Robert Rotenberg delivers a courtroom drama that successfully evokes the multicultural city of Toronto even as it keeps readers on the edges of their seats. In the tale, the "Voice of Canada" radio host confesses to murder-but the case is far from closed. "Rotenberg also fires sly and funny barbs at political correctness and bureaucratic inanity."-Booklist, starred review